Faktor Ekonomi dan Agama Sebagai Salah Satu Faktor Pendorong Asimilasi Arab-Melayu Palembang - Apriana, Apriana (Tanjak: Sejarah dan Peradaban Islam, 2021)
The importance of the position of Arabs in the process of Islamization and trade in Palembang had a positive impact on the existence of Arabs in Palembang and allowed assimilation between Arabs and the Malay population of Palembang to occur without experiencing obstacles. This assimilation process that has been going on for so long has finally produced a distinctive culture. In the assimilation process, there are factors that support the assimilation process so that the assimilation process goes without a hitch. In this study, the issue of economic and religious factors is the supporter of the formation of the Palembang Malay-Arab assimilation. This research includes descriptive qualitative research, data collection is done through interviews, participant observation and documentation related to the research. After the data is collected then it is analyzed through the process of data reduction, data display and drawing conclusions (verification). The results of this study reveal that economic factors are one of the driving factors for the process of cultural assimilation of the Arabs and Malays of Palembang, because ethnically, the economic conditions of the Palembang people seem balanced so that the assimilation process can run smoothly without obstacles. Furthermore, the religious factor is also one of the factors in supporting the process of assimilation of the Arab-Malay Palembang. Religion is one of the structural parameters in Palembang society that can facilitate the process of assimilation of Arab-Malay people. Through religious similarity, it can facilitate the creation of Arab-Malay assimilation in Palemban because all Arabs are Muslim and the majority of Palembang people are Muslim. Here the structure of Islam as the majority religion has a unifying function so that it has allowed the process of assimilation of cultural people in a wide-degree (large-degree) frequency.